An Investigation of the Compliment Responses in Cross-Cultural Communication between Persian and Arabic Native Speakers as EFL Learners - Zeinab Azadbakht; Hadi Heidari (English Lecturers and Teachers Association (ELTA), 2026)
The study followed an explanatory mixed-methods design and investigated the effect of cultural differences on the cross-cultural communication (CR) pattern. For this aim, sixty Persian and Arabic Native Speakers as EFL Learners were divided into two groups based on their native languages, each group with thirty participants. At the onset of the study, the Oxford Placement Test examined the homogeneity of the groups in terms of language proficiency. Moreover, a test consisting of 12 WDCTs was utilized to assess the initial ILP competence of the participants. All of the learners responded to the items individually. Finally, based on Holmes’ (1986) classification consisting of three main categories (i.e., Accept, Reject, and Evade), the collected data were coded by three raters as a Persian and an Arabic native speaker, who were professors of Applied Linguistics, as well as the researcher herself. The findings of the quantitative phase indicated that Arabic speakers are generally more inclined to acknowledge compliments directly, while Persian speakers tend to downplay praise or respond it indirectly, which reflects deeper cultural norms around humility and face-saving communication. The results of the qualitative phase showed that the speech events of CRs are determined by the shared beliefs and values of the speech community and they are contextually restricted within the communicative patterns, which can only be interpreted as parts of the social and cultural context. However, both groups indicated that they struggled with the pragmatic norms of English, such as how to appropriately make requests, apologize, or refuse offers. The findings indicate that due to the inherent socio-cultural differences and implemented strategies of speakers of different languages, they need to acquire the norms of the target culture in order to respond to compliments in an L2. To put it another way, the interlocutors need to find ways to meet the social expectations, in line with the target culture norms. Keywords : Compliment Responses; Cross-Cultural Communication; Interlanguage Pragmatic; Persian and Arabic Native Speakers; WDCT